Analysis of Project Activities for Strengthening Pancasila Student Profiles (P5) through the Manufacturing of VCO Products - Syahrial Ayub; Agustina Agustina; Muh. Makhrus (Balai Publikasi Indonesia, 2022)
This study aims to analyze the stages of making Virgin Coconut Oil (VCO) at SMAN 1 Sekotong, West Lombok, NTB Indonesia. Making Virgin Coconut Oil (VCO) products is one of the Projects to Strengthen Pancasila Student Profiles (P5) in the independent curriculum. The research objectives were achieved with qualitative descriptive methods and what was found during the research. Data was collected by observation, interviews with teachers directly involved in this project. The results of the analysis show the stages of making Virgin Coconut Oil (VCO) starting from selecting good coconuts, making coconut milk, separating the first coconut milk, and separating the second coconut milk and finally getting Virgin Coconot Oil (VCO).